Maternal immune activation as a risk factor for psychiatric illness in the context of the SARS-CoV-2 pandemic - Lins, Brittney (Elsevier, 2021)
Inflammation, due to infectious pathogens or other non-infectious stimuli, during pregnancy is associated with elevated risk for neurodevelopmental disorders such as schizophrenia and autism in the offspring. Although historically identified through retrospective epidemiologic studies, the relationship between maternal immune activation and offspring neurodevelopmental disease risk is now well established because of clinical studies which utilized prospective birth cohorts, serologically confirmed infection records, and subsequent long-term offspring follow-up. These efforts have been corroborated by preclinical research which demonstrates anatomical, biochemical, and behavioural alterations that resemble the clinical features of psychiatric illnesses. Intervention studies further demonstrate causal roles of inflammatory mediators, such as cytokines, in these long-lasting changes in behaviour and brain. This review summarizes a selection of maternal immune activation literature that explores the relationship between these inflammatory mediators and the neuropsychiatric-like effects later observed in the offspring. This literature is presented alongside emerging information regarding SARS-CoV-2 infection in pregnancy, with discussion of how these data may inform future research regarding the effects of the present coronavirus pandemic on emerging birth cohorts.